Shariah Compliance Level of Islamic Banks in Asia and Its Implications on Financial Performance and Market Share - Nidyanti, Adelia; Siswantoro, Dodik (European Journal of Islamic Finance, 2022)
This study proves the influence of shariah compliance level of Islamic banks in Asia on financial performance and market share. This study is descriptive quantitative.The sample is 62 Islamic banks located in Asia with observation years from 2016 to 2018. This study proves the average level of shariah compliance of Islamic banks in Asia is compliant. The results cannot prove that the shariah compliance level of Islamic banks in Asia has an influence on the financial performance and market share. The samples in this study are limited and the observation year is short. The results of this study can be considered by stakeholders in investing their funds. Regulators in Indonesia are expected to be able to make deeper regulations for Islamic banks. This study contributes the Islamic economic literature because the number of studies that look at the level of sharia compliance with one measurement in the Asian region and see the implications of the level of sharia compliance on financial performance and market share is still limited.